Nurses' Moral Distress, Burnout, and Intentions to Leave: An Integrative Review. Issue 3 (July 2019) - Karakachian, Angela; Colbert, Alison
Abstract : ABSTRACT: Moral distress has been widely addressed across the nursing profession and within other disciplines. Forensic nurses are a vital part of the nursing profession as they care for complex patients who may suffer physically and psychologically. However, forensic nurses' moral distress in the context of caring for victims of violence has not been addressed. This integrative review of the literature reveals the consequences of moral distress on the nursing workforce particularly regarding nurses' burnout and intentions to leave their jobs. Turnover contributes to the country's critical shortage of nurses, which affects the quality of care patients receive and increases the costs for healthcare institutions. Abstract : Supplemental digital content is available in the text.